2019
DOI: 10.1186/s11671-019-2910-5
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Flexible Asymmetric Supercapacitor with Good Cycling Performance and Ultra-Power Density by Electrode Materials of Core-Shell CoNiO2@NiAl-Layered Double Hydroxide and Hollow Spherical α-Fe2O3

Abstract: High electrochemical performance of asymmetric supercapacitor (ASC) depends on exquisite nanostructure design and synthesis of electrodes, including structural controllable design and synthesis of high theoretical performance materials and nanocomposite materials. Herein, a template-free hierarchical core-shell nanostructure of CoNiO2@NiAl-layered double hydroxide (NiAl-LDH) and α-Fe2O3 with a hollow spherical structure composed of nanoparticles are successfully prepared. The CoNiO2@NiAl-LDH as the cathode ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…These GCD curves displayed non-linear shapes, thus, exposing the faradaic behaviour of both electrodes. 53 Fig. 9 displayed the specific capacity at different scan rates for all the samples.…”
Section: Resultsmentioning
confidence: 99%
“…These GCD curves displayed non-linear shapes, thus, exposing the faradaic behaviour of both electrodes. 53 Fig. 9 displayed the specific capacity at different scan rates for all the samples.…”
Section: Resultsmentioning
confidence: 99%
“…All prominent standard diffraction peaks conforming the formation of CoNiO 2 have been observed in recorded XRD spectra (JCPDS No. 10-0188) [20][21][22]. Diffraction peaks at 37°, 43°, and 63°are ascribed to (111), (200), and (220) planes of the CoNiO 2 phase, and a minor diffraction peak at around 45°can be indexed to the NiCo 2 O 4 phase (JCPDS No.…”
Section: Structural Analysismentioning
confidence: 99%
“…High-performance asymmetric SCs have been fabricated using Fe 2 O 3 as the negative electrode. For instance, Zhang et al 162 reported the electrochemical performance of an asymmetric SC manufactured by using oxides and layered double hydroxides (LDHs). The devices consisted of a core–shell structured CoNiO 2 @NiAl-LDH composite as positive and α-Fe 2 O 3 as negative electrode.…”
Section: Metal Oxide-based Materials For Supercapacitorsmentioning
confidence: 99%